1990
DOI: 10.1002/j.1460-2075.1990.tb07529.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of recombinant human factor IX expressed in transgenic mice and in derived trans-immortalized hepatic cell lines.

Abstract: Transgenic mice were generated in which 5 kb of the 5′ flanking promoter region of the human Factor IX (FIX) gene fused to various FIX constructs (gene, minigene and cDNA) were stably integrated in the germ line. Several transgenic mouse lines expressed high circulating levels of active and correctly processed recombinant human FIX. The presence of at least one FIX intron had a positive effect on the expression. The FIX transgenes were expressed in a tissue‐specific manner in the liver of transgenic mice. By c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 41 publications
3
37
1
Order By: Relevance
“…This is consistent with in vitro data generated by us 47 and by others 48 in nonhepatocyte cell types, showing that the cell's capacity to execute critical posttranslational modifications (eg, ␥-carboxylation) can be saturated, resulting in production of F.IX protein with reduced specific activity. Our results are at odds with data published on the first F.IX transgenic mice by Jallat et al, 49 who found that mice expressing up to 25 g/mL hF.IX had normal specific activity. These investigators were attempting to measure specific activity of hF.IX on a background of normal levels of murine F.IX.…”
Section: Discussioncontrasting
confidence: 99%
“…This is consistent with in vitro data generated by us 47 and by others 48 in nonhepatocyte cell types, showing that the cell's capacity to execute critical posttranslational modifications (eg, ␥-carboxylation) can be saturated, resulting in production of F.IX protein with reduced specific activity. Our results are at odds with data published on the first F.IX transgenic mice by Jallat et al, 49 who found that mice expressing up to 25 g/mL hF.IX had normal specific activity. These investigators were attempting to measure specific activity of hF.IX on a background of normal levels of murine F.IX.…”
Section: Discussioncontrasting
confidence: 99%
“…These results indicate that, at least in vitro, this distal sequence is not involved in regulating grik5 transcription and tissue-specific expression. Transcriptional regulatory elements of eukaryotic genes are found not only in their 5Ј upstream region, but also within their introns (25)(26)(27)(28)(29)(30)(31)(32)(33)(34). These sequences can act as transcriptional enhancers (27,28,30,33) or can be required for appropriate tissue-or cell-specific expression (25,26,34).…”
Section: Discussionmentioning
confidence: 99%
“…A 251 bp sequence of the genomic human gA-I containing the complete 5 0 -UTR including the first apo A-I intron was subcloned to generate pTG14681-AT.A-I intron.cDNA.E 4 . Multiple sublconing steps using a truncated human FIX intron 12,53,54 isolated from pGEM-FIX-intron by ClaI and NotI digestion led to the formation of pTG14681-AT.FIX intron.cDNA.E 4 .…”
Section: Construction Of Expression Cassettes For Hepatocytedirected mentioning
confidence: 99%